Structural insights into cortical morphometry and erectile dysfunction: a Mendelian randomization and genetic correlation study - Chen Fu; Tianhong Wang; Qihai Wan; Jiacheng Jiang; Xiaofeng Ou (Journal of Men's Health)
Previous studies have disclosed that abnormal brain dynamics are involved in erectile dysfunction (ED). However, the association of cortical morphometry with ED remains unclear. To investigate the association of the surface area and thickness of the total cerebral cortex and 34 regions with ED, this Mendelian Randomization (MR) study was performed. Summary statistics of the surface area and thickness of cerebral cortex and ED were retrieved from previous genome-wide association studies. Genetic correlations between cortical morphometry and ED were evaluated by high-definition likelihood and linkage disequilibrium score regression (LDSC). Causal inference was made by the inverse variance weighting (IVW) estimator, supplemented by the MR-Egger, Weighted median, Maximum likelihood, MR. robust adjusted profile score, and MR-Pleiotropy Residual Sum and Outlier methods. The effect size of the surface area was scaled according to the standard deviation (SD). For surface area, the IVW estimator showed that a one SD increase of the entorhinal cortex and superior frontal cortex corresponded to a 1.25-fold (95% confidence interval (CI) = 1.03–1.53, p = 0.026) and a 1.24-fold (95% CI = 1.02–1.50, p = 0.031) risk of ED, respectively. LDSC regression found a significant genetic correlation between the surface area of the entorhinal cortex and ED (rg = 0.093, p < 0.05). For thickness, the IVW method revealed that genetically proxied one millimeter increase of the inferior temporal cortex and paracentral cortex led to a 6.58-fold (95% CI = 1.16–37.14, p = 0.033) and a 7.99-fold (95% CI = 1.17–54.49, p = 0.034) risk of ED, respectively. The other five methods also supported these findings. No heterogeneity or pleiotropy was detected in the instrumental variables. This study supports that genetically proxied cortical morphometry is associated with an elevated risk of ED. This study provides new insights into the etiology of ED.